2022
DOI: 10.48550/arxiv.2202.06290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermodynamic and Optical Behaviors of Quintessential Hayward-AdS Black Holes

A. Belhaj,
M. Benali,
H. El Moumni
et al.

Abstract: Motivated by Dark Energy (DE) activities, we study certain physical behaviors of the quintessential Hayward-AdS black holes in four dimensions. We generalize some physical properties of the ordinary Hayward AdS black holes without the dark sector. We elaborate a study in terms of the new quantities c and ω q parametrizing the dark sector moduli space. We investigate the effect of such parameters on certain thermodynamic and optical aspects. To show the quintessential thermodynamic behaviors, we first reconside… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…This dark silhouette is known as black hole shadow from the outside observer. Note that the shadows of spherically symmetric black holes are circular [18][19][20][21][22], but for the spinning black holes their shadows are actually deformed [23][24][25][26][27][28]. Moreover, the photon region of gravitational lensing also provides key properties in the black hole shadow.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This dark silhouette is known as black hole shadow from the outside observer. Note that the shadows of spherically symmetric black holes are circular [18][19][20][21][22], but for the spinning black holes their shadows are actually deformed [23][24][25][26][27][28]. Moreover, the photon region of gravitational lensing also provides key properties in the black hole shadow.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Hawking and Page had shown the theoretical evidence of the certain transition in the phase space for the Schwarzschild-AdS black hole [40]. The first-order phase transition of the charged Reissner Nordstrom-AdS (RN-AdS) black hole has been studied in different backgrounds including Dark Energy (DE) and Dark Matter (DM) [22,41,42]. In this way, the shadows and the deflection angle of the light rays by black holes in arbitrary dimensions have been discussed in [22,25,41,43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In four dimensions, it has been shown that the non-rotating black hole solutions exhibit a perfect circular geometry where the size can be controlled by certain parameters as the charge [7,20,21]. For the rotating black holes, however, the circular configuration is deformed and distorted generating non trivial shapes including D and cardioid ones [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Hawking and Page (HP) have provided theoretical evidence for the existence of certain transitions in the phase space of the (non-rotating uncharged) Schwarzschild-AdS black hole. A first order phase transition in the charged (non-rotating) Reissner Nordstrom-AdS (RN-AdS) black hole space-time has been studied in different backgrounds including Dark Energy (DE) and Dark Matter (DM) [20,32,33]. The effect of such a dark sector on the optical aspect has been also investigated for different backgrounds.…”
Section: Introductionmentioning
confidence: 99%